2002
DOI: 10.1007/s11894-002-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

HIV1 and the gut in the era of highly active antiretroviral therapy

Abstract: The gut and its gut-associated lymphoid tissue serve as a preferential site for HIV1 entry, active viral replication, reservoir, and HIV-mediated CD4 cell apoptosis. The widespread use of highly active antiretroviral therapy (HAART) has resulted in a significant decrease in the incidence of opportunistic enteric pathogens as a consequence of immune recovery. Nonetheless, patients with advanced HIV1 disease who were recently diagnosed or have poor response to HAART can still suffer from opportunistic infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 54 publications
1
28
0
1
Order By: Relevance
“…Furthermore, our targeting-strategy induces mucosal and systemic immunity against a tumor model. We believe that our findings may have implications in the generation of CD8 T cells against gut infections including HIV, which uses the gut as a reservoir (13).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, our targeting-strategy induces mucosal and systemic immunity against a tumor model. We believe that our findings may have implications in the generation of CD8 T cells against gut infections including HIV, which uses the gut as a reservoir (13).…”
Section: Discussionmentioning
confidence: 83%
“…It is generally thought that CTL are critical for immunological curing of HIV infection (12,13). We previously showed that the parenteral immunization of mice using this targeting anti-MAdCAM Ab leads to the development of a secretory IgA response in the gut, a systemic IgG response, as well as T cell cytokine and proliferative response (14).…”
mentioning
confidence: 99%
“…While the disease state of HIV/AIDS patients was not recorded as part of this study, CD4 þ T-cell depletion of GALT (gutassociated lymphoid tissue) is an early event in the pathogenesis of human HIV infection and restoration is delayed even after highly active antiretroviral therapy (Guadalupe et al, 2003). GALT harbors the majority of T lymphocytes in the human body (Nannini and Okhuysen, 2002), further suggesting that the T-cell-mediated adaptive immune response could be responsible for the observed microbiota changes in transplant recipients and HIV/AIDS patients samples and could be important for hostcontrolled GI tract homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Gut-associated lymphoid tissue (GALT) harbors the vast majority of lymphoid tissue in the body and has been shown to be a persistent viral reservoir as well as an important site for host-pathogen interactions in HIV-1 infection (4,7,14). Since intestinal biopsy samples from patients can be obtained repeatedly, GALT can serve as an accessible source of mucosal lymphoid tissue to examine the direct effects of HAART on the kinetics of CD4 ϩ T-cell homeostasis and suppression of viral loads.…”
mentioning
confidence: 99%